Severe eosinophilic asthma: from the pathogenic role of interleukin-5 to the therapeutic action of mepolizumab - Pelaia C; Vatrella A; Busceti MT; Gallelli L; Terracciano R; Savino R; Pelaia G (Dove Medical Press, 2017)
Corrado Pelaia,1 Alessandro Vatrella,2 Maria Teresa Busceti,1 Luca Gallelli,3 Rosa Terracciano,3 Rocco Savino,3 Girolamo Pelaia1 1Department of Medical and Surgical Sciences, Section of Respiratory Diseases, University “Magna Græcia” of Catanzaro, Catanzaro, 2Department of Medicine, Surgery and Dentistry, Section of Respiratory Diseases, University of Salerno, Salerno, 3Department of Health Science, University “Magna Græcia” of Catanzaro, Catanzaro, Italy Abstract: Mepolizumab is an anti-interleukin-5 (IL-5) humanized monoclonal antibody that has been recently approved as an add-on biological treatment for severe eosinophilic asthma, by both the US Food and Drug Administration (FDA) and the European Medicines Agency (EMA). Moreover, mepolizumab is also currently included within the step 5 of the Global Initiative for Asthma guidelines, as an add-on therapy for severe uncontrolled asthma. The relevant therapeutic benefits detectable in patients with refractory eosinophilic asthma receiving mepolizumab depend on the pivotal pathogenic role played by IL-5 in these subjects. Indeed, IL-5 is the key cytokine responsible for maturation, activation, proliferation, and survival of eosinophils. Therefore, IL-5 represents a strategic molecular target for anti-eosinophilic treatments. By selectively inhibiting the biological actions of IL-5, mepolizumab provides a valuable therapeutic option for patients with severe eosinophilic asthma, refractory to standard treatments including inhaled and even systemic corticosteroids. In particular, the very important advantages linked to the use of mepolizumab in these difficult-to-treat asthmatic individuals have been well documented by several different trials performed worldwide. Keywords: IL-5, severe eosinophilic asthma, mepolizumab